(untitled) (Eurasian Journal of Learning and Academic Teaching, 2025)
This paper analyzes the experience of teaching foreign languages to students majoring in sports using modern methodologies. Experimental sessions were conducted in two groups (experimental and control). The results demonstrate the effectiveness of communicative and contextual approaches in enhancing the foreign language proficiency of sports students